2017
DOI: 10.1039/c7dt00010c
|View full text |Cite
|
Sign up to set email alerts
|

Gradual modification of ITO particle's crystal structure and optical properties by pulsed UV laser irradiation in a free liquid jet

Abstract: Indium tin oxide (ITO) particle coatings are known for high transparency in the visible, good conductive properties and near-infrared absorption. These properties depend on ITO particle's stoichiometric composition, defects and size. Here we present a method to gradually change ITO particle's optical properties by a simple and controlled laser irradiation process. The defined irradiation process and controlled energy dose input allows one to engineer the absorption and transmission of coatings made from these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We processed 500 mg of powder for each of the 70 samples (photographs of dried laser-modified materials are shown in Figure ). We laser-irradiated 500 mL of the aqueous particle dispersions (1 g L –1 ) in a home-built liquid-jet flow reactor (Figure S1), which is described in detail in refs , , , , and . For conditions of high thermal load and isochoric melting, we employed a diode-pumped solid-state laser system (AVIA, Coherent Inc.) that operated at 85 kHz with 40 ns pulse length and emitted 355 nm pulses at a power of 19.4 W (denoted as ns–355 nm laser).…”
Section: Methodsmentioning
confidence: 99%
“…We processed 500 mg of powder for each of the 70 samples (photographs of dried laser-modified materials are shown in Figure ). We laser-irradiated 500 mL of the aqueous particle dispersions (1 g L –1 ) in a home-built liquid-jet flow reactor (Figure S1), which is described in detail in refs , , , , and . For conditions of high thermal load and isochoric melting, we employed a diode-pumped solid-state laser system (AVIA, Coherent Inc.) that operated at 85 kHz with 40 ns pulse length and emitted 355 nm pulses at a power of 19.4 W (denoted as ns–355 nm laser).…”
Section: Methodsmentioning
confidence: 99%
“…The main goal is to understand and develop photon‐induced defect formation strategies and understand how different types and densities of defect sites contribute to the catalytic activity in different reaction scenarios. Despite the studies on single crystalline oxide surfaces and bulk materials as well as nanomaterials, no general mechanism on laser‐based defect generation in the liquid is available to date . From the present knowledge, the most important laser parameters determining defect formation in terms of electron excitation and occurring thermal stress during and after laser irradiation are: laser pulse duration, laser fluence, the particle mass‐specific laser energy dose and laser wavelength .…”
Section: Future Prospects: Laser‐based Defect Engineeringmentioning
confidence: 99%
“…Due to the electron deficiency, a positively charged particle remains, which undergoes spontaneous fission once the Coulomb forces exceed the cohesive forces of the particle. , Researchers have reported that the size of the resulting particles after a CE is only dependent on the properties of the colloid (concentration and matrix) and does not scale with the laser fluence once the onset threshold for the CE is exceeded. , On the other hand, if the temperature within the particle becomes slightly higher than the boiling temperature of gold and the laser pulse duration is long enough to allow the electrons and the lattice to reach thermal equilibrium, a photothermal mechanism for size reduction has also been observed and reported in the literature, known as the heating–melting–evaporation (HME) mechanism. ,,, Accordingly, during nanosecond (ns) pulse irradiation, the electron–phonon and the electron–electron relaxation for gold occur on time scales more than 2–3 orders of magnitude shorter than the pulse duration so this mechanism is suspected to be dominant during fragmentation with ns pulses. , Since the boiling process is very slow in terms of ns time scales, with removal rates of less than 0.1 monolayers per ns, superheating of the nanomaterial must be considered. , Once the temperature of the educt particle exceeds the spinodal temperature in a range of ∼80 to ∼90% of the critical temperature, ,, explosive boiling of the superheated liquid droplet is likely to occur. To date, this mechanism has only been discussed in terms of laser ablation or fundamental theory and has rarely been addressed as a potential laser fragmentation mechanism. According to Miotello and Kelly, the essence of phase explosion is the homogeneous nucleation of vaporous material throughout the molten ablation zone once the spinodal temperature is reached, which leads to ejection and spillage , and the formation of bimodal size distributions .…”
Section: Introductionmentioning
confidence: 99%
“…To date, this mechanism has only been discussed in terms of laser ablation or fundamental theory and has rarely been addressed as a potential laser fragmentation mechanism. According to Miotello and Kelly, the essence of phase explosion is the homogeneous nucleation of vaporous material throughout the molten ablation zone once the spinodal temperature is reached, which leads to ejection and spillage , and the formation of bimodal size distributions . To the best of our knowledge, this scenario has not been modeled in terms of a fragmentation process of spherical nanomaterials.…”
Section: Introductionmentioning
confidence: 99%